Linking Marine Science to Industry: One Building Block - Ellis, Kathleen (Maine Policy Review, 1997)
All involved in the work to develop Maine’s marine industry are united in the view that partnerships are paramount in maximizing the potential of this resource for the benefit of the state’s economy in a global marketplace. One entity with experience in the arena of working in collaboration with the private and public sectors is the University of Maine, which now is attempting to develop its role within the state’s marine industry further by becoming the home of a new School of Marine Sciences. Kathleen Ellis in this commentary offers some historical perspective on the university’s place in the state’s marine science equation, some of its public-private partnership success stories, and its aspirations for the future.
Keywords: Maine; marine industries; Maine Sea Grant